Evaluation of Bioactive Compound from Cashew Apple Juice by Gas Chromatography–Mass Spectrum Analysis: Evaluation of Bioactive Compound from Cashew Apple Juice by Gas Chromatography–Mass Spectrum Analysis - Sivagurunathan, P. (International Journal of Pharmaceutical & Biological Archive, 2019)
Cashew, Anacardiu moccidentale L. belongs to the family Anacardiaceae, it originates from south and central America. It produces a pseudocarp on which the nut is attached. This study was aimed to investigate the presence of bioactive phytochemical constitutions of A. moccidentale. A. moccidentale L. of methanolic extracts gives up to different phytocomponents was confirmed by gas chromatography–mass spectrum analysis. The bioactive compounds such as 9,12-octadecadienoic acid (Z, Z)-, tetradecanoic acid, and 9-octadecadienoyl acid (Z, Z)- were also present in cashew apple (CA). However, these compounds are used in same ayurvedic medicine of antimicrobial, anti-inflammatory, anticholesterol, and anticancer activities. The results ensured that the biowaste CA is a good source of various bioactive compounds which can be used to develop nutritious value-added food and beverages.